Multiscale analyses of the damage of composite rocket motor cases - Liu, Zai; Hui, Weiwei; Chen, Guoqing; Cao, Peng (Frontiers in Materials, 2023)
As one of the key components of solid rocket motors (SRMs) and launch vehicles (LVs), the deformation and damage of the composite rocket motor case (CRMC) can directly affect the effectiveness of the SRMs. Therefore, it is particularly important to analyze the damage failure of composite cases. As the analysis remains complex due to the different failure modes of composites at different scales, this paper applies multiscale analysis methods to CRMC damage. A multiscale mechanical model of CRMC is established, and data transfer between the microscale, mesoscale, and macroscale models is achieved using submodel techniques. In this paper, CRMC was finely modeled, and the thickness and carbon fiber angle of each fiber winding layer were accurately described. Additionally, the results of hydrostatic tests and numerical calculations were compared to verify the validity of the modeling method. The stress levels of the material at macroscale, mesoscale, and microscale scales were obtained through numerical calculations, and the microscale damage failure behavior of the material under the internal pressure load of the composite shell was predicted by combining the strength assessment criterion.